2007
DOI: 10.1111/j.1750-2659.2007.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive retroviral pseudotype assay for influenza H5N1‐neutralizing antibodies

Abstract: Background  The World Health Organisation (WHO) recommended the development of simple, safe, sensitive and specific neutralization assays for avian influenza antibodies. We have used retroviral pseudotypes bearing influenza H5 hemagglutinin (HA) as safe, surrogate viruses for influenza neutralization assays which can be carried out at Biosafety Level 2. Results  Using our assay, sera from patients who had recovered from infection with influenza H5N1, and sera from animals experimentally immunized or infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
149
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 28 publications
1
149
0
Order By: Relevance
“…The potential for broad-spectrum protection was first evaluated by an HI assay as well as by a neutralization assay using HA-pseudotyped viruses. As has been reported (33), results from such in vitro assays do correlate with in vivo protection against lethal virus challenges. Indeed, we observed that antisera to pCHA5 had broad activity in HI assays when tested against H5N1 viruses, although the activity against clades 2.1 and 2.3 was weaker or variable (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The potential for broad-spectrum protection was first evaluated by an HI assay as well as by a neutralization assay using HA-pseudotyped viruses. As has been reported (33), results from such in vitro assays do correlate with in vivo protection against lethal virus challenges. Indeed, we observed that antisera to pCHA5 had broad activity in HI assays when tested against H5N1 viruses, although the activity against clades 2.1 and 2.3 was weaker or variable (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…The HBV surface glycoprotein is unlike other viral glycoproteins tested to date (Moller-Tank & Maury, 2015;Temperton et al, 2007;Wright et al, 2009;Zimmer et al, 2014) in its failure to produce infectious pseudoparticles in human embryonal kidney cells (293T), requiring a liver cell background for infectious particles genesis. Our results show that whilst NTCP does play an essential role in HBVpp entry, it is unlikely to be the sole receptor facilitating infection.…”
mentioning
confidence: 99%
“…This system has been used to study the entry pathways of a range of viruses, including human immunodeficiency virus (HIV), hepatitis C virus (HCV), pathogenic avian influenza and Ebola, offering a rapid and reproducible analysis of the viral glycoprotein-receptor interactions (Moller-Tank & Maury, 2015;Temperton et al, 2007;Wright et al, 2009;Zimmer et al, 2014). Previous reports showed that lentiviral HBVpps were infectious for human hepatocytes; however, given the limited knowledge of internalization pathways at the time, the receptor dependency was not studied (Chai et al, 2007;Sung & Lai, 2002).…”
mentioning
confidence: 99%
“…Only structural genes that enable the generation of virus particles, and a gene for reverse transcription and integration of a reporter gene into the target cell genome of choice, are used in PV production (Temperton et al, 2007). When using a luciferase reporter gene, luminescence acts as an indirect measure for virus infectivity.…”
Section: Pseudotype Virus Neutralization Assay (Pvna) (A) Principles mentioning
confidence: 99%